Use of Weather Forecast Information among Maize Farmers in Kwara State, Nigeria - Ololade Latifat Abdulrahman; Olayinka Jelili Yusuf; Sola Emmanuel Komolafe; Abdullateef Adeshina Abdulrahman; Stephanie Mngusonum Ukpi (Journal of Agricultural Extension)
This study assessed the use of weather forecast information for maize production in Kwara State. A random sampling technique was used to select 160 maize farmers. Through a structured interview schedule, data were collected and analysed using mean, percentages, standard deviation and Pearson product-moment correlation. Findings revealed that 68% of the respondents had a favourable perception towards the use of weather forecast information, 18% had an unfavourable perception while 14% were neutral. Farmers accessed weather forecast information mainly from friends and family (=3.19) and personal experience (=3.16). Seasonal rainfall prediction (=2.73) and temperature (=2.69) were the most used weather forecast information.  Technicality of applying the information (=2.54), inadequate internet access (=2.53) and poor communication (=2.39) were constraints to use.  Correlation results revealed education (r = 0.35) and farming experience (r = 0.31) to be positively significant with access to weather forecast information. Similarly, education (r = 0.21) was positively significant with usage while age (r = -0.32) had negative significance. Encouraging maize farmers to utilize weather forecast information, especially the impact-based ones (flood, windstorm, drought) to make decisions and plans for their farming activities and training on the effective application of weather forecast information  to address farmers’ specific problems.